Development of Cocoa Drier - Abdassalam M (Department of Agricultural Engineering, College of Horticulture, 1985)
An investigation for the development of an electrically heated, multistage, agitation type cocoa drier, suitable for the Kerala conditions for drying of cocoa beans without impairing the quality, was conducted in the Agricultural Engineering Department of the College of Horticulture under the Kerala Agricultural University. The mini box fermentation method developed in Kerala Agricultural University was selected for fermentation of the beans. The fermented cocoa beans were dried in the sun. The process of sun drying continued upto seven days. The pH of dried beans was 5.2, which was very close to the pH range, 5.3 to 5.5 for good quality beans as per international standards. Hence, the quality of the beans was considered satisfactory.